ETHICAL ASPECTS OF DICTIONARIES. THE ROLE OF DICTIONARIES IN LANGUAGE CHANGE (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: This article explores the ethical dimensions of lexicology, emphasizing the principles that guide the study and compilation of dictionaries and lexical resources. It highlights the importance of inclusivity and representation, arguing that dictionaries should reflect the diversity of human communication by incorporating words from various dialects, cultures, and gender-neutral terms. The discussion further underscores the necessity of cultural sensitivity, urging lexicographers to avoid perpetuating stereotypes and to promote a respectful linguistic landscape. The article also addresses accuracy and reliability in dictionary definitions, emphasizing the need for precise language that captures evolving usage and emerging words.Additionally, it examines the social impact of language, focusing on how ethical lexicography can promote social justice, support endangered languages, and empower marginalized voices. The role of research ethics is also highlighted, stressing the importance of obtaining informed consent and handling language data responsibly. Finally, the tension between prescriptive and descriptive approaches to language is analyzed, advocating for a descriptive framework that respects linguistic diversity. Overall, this article posits that ethical considerations in lexicology are vital for creating resources that honor the complexity of language and its profound influence on society.